Deep Brain Stimulation Associated Gliosis: A Post-mortem Study - Vedam-Mai, Vinata (Parkinsonism Relat Disord, 2018)
BACKGROUND: DBS is a well-established therapy for patients with PD and is an emerging therapy for other neuropsychiatric disorders. Despite the rise in DBS usage, relatively little is known about the tissue and cellular responses to DBS. PURPOSE: To examine post-mortem effects of DBS leads by objectively quantifying gliosis around the distal DBS lead tip. METHODS: The UF DBS Brain Bank repository currently has 64 brains, of which 18 cases met criteria for this study. RESULTS: The average patient age was 54.88± 13.43 years (mean ± SD), male:female ratio was 3:1, average disease duration was 20.70 ± 6.36 years and average DBS duration was 7.26 ± 6.36 years. Microscopic evaluation revealed tissue reaction and astrocytic responses to the lead. Significant fibrosis was seen in n=2 brains and prominent microglial response in n=1. Mean gliotic collar measured from H&E and GFAP staining was 122.5 microns and 162.5 microns, respectively. Mean gliotic thickness at the DBS electrode lead tip was 119.13 ± 64.29 μm for patients receiving DBS for 0–5 years, 127.85 ± 94.34 μm for 5–10 years and 111.73 ± 114.18 μm for patients with DBS >10 years. Kruskal-Wallis one-way analysis of variance (ANOVA) revealed no statistically significant differences between DBS duration and amount of gliosis. CONCLUSIONS: This study revealed that approximately three out of four post-mortem DBS cases exhibited pathological evidence of a glial collar or scar present at the ventral DBS lead tip. The amount of gliosis was not significantly associated with duration of DBS. Future studies should include serial sectioning across all DBS contacts with correlation to the volume of tissue activation and to the clinical outcome.